Host-Guest Polymer Complexes - Alan Edward Tonelli (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
I enthusiastically invite you to contribute to a Special Issue of the open-access journal Polymers, focusing on "Host-Guest Polymer Complexes", which I and two of my former PhD students, Drs. Alper Gurarslan and Ganesh Narayanan, are editing. We hope to include papers describing the syntheses, characterization, and use of host-guest polymer complexes, as well as factors that are important to their formation. Submissions that describe unusual and unique applications of host-guest polymer complexes using hosts other than traditional ones: cyclodextrins, cucurbiturils, urea, thiourea, cyclotriphosphazines, etc., are particularly encouraged. I hope that you accept our invitation to make this Special Issue one that will introduce, effectively summarize, and increase interest in this important area of polymer science.